iNOS Associates With Poor Survival in Melanoma: A Role for Nitric Oxide in the PI3K-AKT Pathway Stimulation and PTEN S-Nitrosylation - Ding, Zhen; Ogata, Dai; Roszik, Jason; Qin, Yong; Kim, Sun-Hee; Tetzlaff, Michael T.; Lazar, Alexander J.; Davies, Michael A.; Ekmekcioglu, Suhendan; Grimm, Elizabeth A. (Frontiers in Oncology, 2021)
We previously showed that inducible nitric oxide synthase (iNOS) protein expression in melanoma tumor cells is associated with poor patient prognosis. Here, we analyzed the association between iNOS and the oncogenic PI3K-AKT pathway. TCGA data show that iNOS and phospho-Akt Ser473 expression were associated significantly only in the subset of tumors with genetically intact PTEN. Employing a stage III melanoma TMA, we showed that iNOS protein presence is significantly associated with shorter survival only in tumors with PTEN protein expression. These findings led to our hypothesis that the iNOS product, nitric oxide (NO), suppresses the function of PTEN and stimulates PI3K-Akt activation. Melanoma cells in response to NO exposure in vitro exhibited enhanced AKT kinase activity and substrate phosphorylation, as well as attenuated PTEN phosphatase activity. Biochemical analysis showed that NO exposure resulted in a post-translationally modified S-Nitrosylation (SNO) PTEN, which was also found in cells expressing iNOS. Our findings provide evidence that NO-rich cancers may exhibit AKT activation due to post-translational inactivation of PTEN. This unique activation of oncogenic pathway under nitrosative stress may contribute to the pathogenesis of iNOS in melanoma. Significance: Our study shows that iNOS expression is associated with increased PI3K-AKT signaling and worse clinical outcomes in melanoma patients with wt (intact) PTEN. Mutated PTEN is already inactivated. We also demonstrate that NO activates the PI3K-AKT pathway by suppressing PTEN suppressor function concurrent with the formation of PTEN-SNO. This discovery provides insight into the consequences of inflammatory NO produced in human melanoma and microenvironmental cells. It suggests that NO–driven modification provides a marker of PTEN inactivation, and represents a plausible mechanism of tumor suppressor inactivation in iNOS expressing subset of cancers.